2003
DOI: 10.1111/j.0742-2822.2003.01126.x
|View full text |Cite
|
Sign up to set email alerts
|

Review of Methods for Texture Analysis of Myocardium From Echocardiographic Images: A Means of Tissue Characterization

Abstract: This review discusses the definition of texture and identifies its utility in echocardiography for characterization of tissue. Methods used for quantification of texture in echocardiography and other disciplines are discussed. Several methodologies, particularly the wavelet method of texture quantification, seem to be promising. Image texture analysis appears to be a fertile area for research in echocardiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 50 publications
0
21
0
1
Order By: Relevance
“…The biological basis of quantitative methods that have been introduced for the ultrasound tissue characterization is represented by the possibility that individual structural components of the myocardium can influence its acoustic properties in different physiologic and pathologic conditions [16]. These methods are essentially represented by radiofrequency (integrated backscatter) [17,18] and echocardiographic gray level (videodensitometry) analysis [19,20].…”
Section: Target Of Ultrasound Diagnosis: Present and Futurementioning
confidence: 99%
“…The biological basis of quantitative methods that have been introduced for the ultrasound tissue characterization is represented by the possibility that individual structural components of the myocardium can influence its acoustic properties in different physiologic and pathologic conditions [16]. These methods are essentially represented by radiofrequency (integrated backscatter) [17,18] and echocardiographic gray level (videodensitometry) analysis [19,20].…”
Section: Target Of Ultrasound Diagnosis: Present and Futurementioning
confidence: 99%
“…Myocardial tissue characterization by ultrasound was first used in 1957 in differentiation of infarcted hearts from normal hearts [31]. This technique is complementary to the conventional echocardiographic method in evaluating the myocardium [7,16,18,[32][33][34][35]. Previous studies showed that CV index enables us to discriminate ischemic [36], hypertensive [9,17], and diabetic [37] hearts from normal myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…20 It is based on the principle that the interaction of ultrasound waves with normal myocardial tissue results in reflected ultrasonic signals that exhibit characteristics different from those obtained when ultrasound interacts with abnormal tissue (eg, fibrotic tissue). 21 These characteristics are amenable to quantification (one of the approaches being the measurement of tissue-integrated backscatter), that defines the myocardial structure and functional attributes. In this regard, an association between alterations in echoreflectivity, namely diminution in the cyclic variation of the backscatter signal, and an increase in fibrous tissue has been shown in the hearts of hypertensive patients.…”
Section: Non-invasive Physical Methodsmentioning
confidence: 99%